2019
DOI: 10.1148/radiol.2019190562
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Electronic Cigarette Aerosol Inhalation on Vascular Function Detected at Quantitative MRI

Abstract: lectronic cigarettes (hereafter, e-cigarettes) deliver nicotine by the electric heating and aerosolization of a flavored solution, or e-liquid (1). E-cigarettes are a public health issue because of their widespread use, especially among teenagers, despite uncertainty about their effect on long-term health (2). Many studies now question whether e-cigarette aerosol inhalation, or vaping, is safe (3-11), and it was found to cause vascular endothelial damage (8,9) and alterations in vascular tone (10,11). The basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 32 publications
2
70
0
Order By: Relevance
“…3,28,29 It is likely, however, that the difference in nicotine absorption from JUUL and conventional e-cig aerosol does not directly dictate the magnitude of the vascular response, which we have already observed to be saturating in this model even by very brief (2 seconds) mainstream exposures to cigarette smoke and IQOS aerosol. 20 While we have reported a positive correlation between the concentration of nicotine in heavily diluted tobacco sidestream smoke and the extent to which FMD is impaired in rats exposed to it, 30 the fact that FMD is still impaired in humans inhaling nicotine-free e-cig aerosol 22 and in rats inhaling marijuana sidestream smoke 19 indicates that the nicotine is not the main driver of this effect.…”
Section: Serum Nicotine Was Highest In Rats That Were Exposed To Juulmentioning
confidence: 85%
See 2 more Smart Citations
“…3,28,29 It is likely, however, that the difference in nicotine absorption from JUUL and conventional e-cig aerosol does not directly dictate the magnitude of the vascular response, which we have already observed to be saturating in this model even by very brief (2 seconds) mainstream exposures to cigarette smoke and IQOS aerosol. 20 While we have reported a positive correlation between the concentration of nicotine in heavily diluted tobacco sidestream smoke and the extent to which FMD is impaired in rats exposed to it, 30 the fact that FMD is still impaired in humans inhaling nicotine-free e-cig aerosol 22 and in rats inhaling marijuana sidestream smoke 19 indicates that the nicotine is not the main driver of this effect.…”
Section: Serum Nicotine Was Highest In Rats That Were Exposed To Juulmentioning
confidence: 85%
“…12,15 Using this technique, we showed that FMD is also impaired in rats by brief exposures to mainstream and sidestream smoke or mainstream aerosols from cigarettes, little cigars, combustible marijuana, and IQOS "heat-not-burn" tobacco products. [17][18][19][20] Acute use of e-cigs 8/30/19 4 with or without nicotine in humans impairs several measures of endothelial function including FMD 21,22 and we have reported that nitric oxide production from cultured endothelial cells is impaired when the cells are incubated in serum from chronic e-cig use. 23 Here we report that acute mainstream exposure to aerosol from JUUL or from previous generation e-cigs using freebase nicotine impairs vascular function comparably to combusted cigarette smoke and delivers considerably more nicotine to the blood on a per puff basis.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…By quantifying macrovascular blood flow dynamically in the feeding artery, the time to peak flow and the duration of forward flow can be measured. These parameters are increased in the presence of PAD (Langham et al, 2013a) and are sensitive to early changes in endothelial function that occur with smoking, aging (Langham et al, 2015), and have recently been shown to be acutely impaired following nicotine-free e-cigarette aerosol inhalation (Caporale et al, 2019).…”
Section: Phase Contrast Mri For Quantification Of Macrovascular Flowmentioning
confidence: 99%
“…Fluids are available that have only flavorings and carrier liquid, but recent reports indicate that these can still cause serious health effects. A new study in human volunteers demonstrates that vaping e‐liquids, even those that do not contain nicotine, can have acute effects on the vascular endothelium, reducing peak blood flow velocity and luminal flow‐mediated dilation in the superficial femoral artery and vein (Caporale et al, ). If such changes were to occur in the uteroplacental circulation of pregnant women, dangerous hypoxic conditions could occur for the embryo/fetus.…”
mentioning
confidence: 99%